Does Finding Cecal Adenoma Increase the Risk of Discovering More and Advanced Adenomas in the Remainder of the Colon?. Issue 9 (September 2022) - Nadeem, Mahum; Parava M, Pratyusha; Bitar, Hussein; Hanafi, Muhammad; Mahmood, Sultan; Saleem, Rabia; Madhoun, Mohammad F.
Abstract : This is the first retrospective study highlighting the association of colonic adenoma location with finding multiple and advanced adenomas in remainder of the colon. Clinically finding a cecal adenoma should prompt endoscopists to be more thorough and vigilant when evaluating the entire colon, specifically on the right side. Abstract: Objectives: Adenomatous polyps are common, occurring in up to 25% of the population older than 50 years of age in the United States. Conflicting data are present in the literature about the impact of specific adenoma locations and the prediction on the number and advanced histology of adenomas elsewhere. With this study we aimed to review the association between cecal adenoma and the risk of discovering more and advanced adenomas in the remainder of the colon. Methods: We performed a retrospective study of 1880 patients who received outpatient colonoscopies between June 2012 and December 2014 at the Veterans Affairs Medical Center in Oklahoma City. The data collected included patient demographics, indications for colonoscopy, smoking history, alcohol use, family history of colon cancer, quality of bowel preparation, number of adenomas, location, size of adenomas, and the histology of adenomas and colon cancer. Results: The mean age of the study population was 61.6 ± 9.4 year, with 95% of the population being men. Cecal adenomas were found in 243 (12.9%) of patients. Patients with cecal adenoma tended to be older (65 ± 7 vs 61 ± 10, P < 0.0001), more likely to be men (97% vs 94%, P = 0.06) and less likely to have a colonoscopy done for screening indication (11% vs. 13%., P = 0.03). After adjusting for age, sex, indication, and quality of bowel preparation, patients with cecal adenoma were found to have a sixfold increase in finding ≥10 other adenomas elsewhere (4.5% vs 0.8% P = 0.0009) and a threefold increase in finding advanced adenomas (17.7% vs 9.9% P = 0.002) in the remainder of the colon. Stratifying by location, the increased risk was more pronounced in the right side (24.7% vs 8.9% P ≤ 0.0001) compared with the left side. Conclusions: Cecal adenoma is associated with an increased risk of finding more and advanced adenomas in the remainder of the colon, especially on the right side; therefore, the discovery of a cecal adenoma should prompt a more thorough evaluation of the entire colon, particularly the right colon.